2016
DOI: 10.1111/cpf.12351
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dual‐energy X‐ray absorptiometry, air displacement plethysmography and A‐mode ultrasound to assess body composition in college‐age adults

Abstract: There was statistical agreement between US and ADP for FM and FFM but lack of agreement for US and ADP when compared to DXA. However, the large limits of agreement between methods warrant caution in generalizing these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
1
18
0
5
Order By: Relevance
“…The present study observed good validity of the ultrasound device when compared to the reference ADP. Previous studies have reported conflicting findings, both good and poor validity, when compared to ADP (Hendrickson et al, 2019;Wagner et al, 2016) and DXA (Johnson et al, 2017;Johnson et al, 2014;Loenneke et al, 2014). Previous studies reported that the BodyMetrix ultrasound device tended to underestimate %BF for males compared to ADP Our analyses of %BF between skinfold callipers and ultrasound showed a significant bias between the two devices with some individual variances, further emphasizing the high susceptibility of human error when using skinfold thickness.…”
Section: Discussionmentioning
confidence: 57%
“…The present study observed good validity of the ultrasound device when compared to the reference ADP. Previous studies have reported conflicting findings, both good and poor validity, when compared to ADP (Hendrickson et al, 2019;Wagner et al, 2016) and DXA (Johnson et al, 2017;Johnson et al, 2014;Loenneke et al, 2014). Previous studies reported that the BodyMetrix ultrasound device tended to underestimate %BF for males compared to ADP Our analyses of %BF between skinfold callipers and ultrasound showed a significant bias between the two devices with some individual variances, further emphasizing the high susceptibility of human error when using skinfold thickness.…”
Section: Discussionmentioning
confidence: 57%
“…Body composition was measured using the BodyMetrix (BMX; BodyMetrix System, BX‐2000, IntelaMetrix, Inc., Livermore, CA), a handheld device which utilizes amplitude‐mode ultrasound technology to measure fat thickness 31 . This newer modality has been validated against well‐accepted modalities, including air displacement plethysmography 31,32 in adults of normal weight, and has been shown to accurately measure (with <1 mm error) fat thickness of intact and dissected cadaveric material in a validation study 33 . In our study, fat thickness was measured at 4 sites: triceps, hip, waist, and thigh on the right side of the body.…”
Section: Methodsmentioning
confidence: 98%
“…Body composition is a key measure of health at the individual and population level (Wells & Fewtrell, 2006). Currently, the most common metric of body composition utilized for disease risk assessment is body mass index (BMI), defined as body mass (kg) divided by height squared (m 2 ; Johnson et al, 2017). Although BMI is a practical metric due to its quick and easy application, it solely describes the relationship between an individual's height and weight and is unable to distinguish between fat-free mass (FFM) and fat mass (FM), thus limiting its utility in active populations with relatively greater amounts of FFM compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…B-mode US produces a 2-D image that is ideal for the assessment of body composition since it allows the user to better determine varying tissues within the image. Importantly, US devices are portable and relatively inexpensive compared with other research-grade body composition devices (Johnson et al, 2017), making them a more practical option for many organizations. However, no standardized method for using US to assess percent body fat has yet been developed, warranting further research (Smith-Ryan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation